Seychelles : 2010 Article IV Consultation and Second Review Under the Extended Arrangement, Request for Rephasing of Disbursements, and Financing Assurances Review-Staff Report; Staff Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Seychelles. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Seychelles's strong stabilization efforts has helped the economy to overcome debt crisis and global recession under the Stand-By Arrangement (SBA). But the authorities need to address monetary policy trade-offs, and financial sector challenges exist. Executive Directors welcomed Seychelles's structural reform agenda, which aims at enhancing public financial and central bank management, strengthening competition and risk management, and reducing the role of the state in the financial system. Directors appreciated Seychelles's strong performance compliance with performance criteria under the economic program, and extended further financing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet